A Study of Ethics and Accounting Education in India: Examining the Role of Ethics Education in Shaping Future Accountants (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Despite the accounting standards and ethical codes guiding the accounting profession, morality and ethics has gone down the drain based on the occurrence of scandals in Enron, World Com, India and similar scandals that have surfaced. In line with this, this study looked into the opinions of accounting lecturers in some Indian universities on whether the teaching of ethics among student accountants can facilitate in instilling ethical behavior in future accountants. These opinions were later tested using the Chi-Square method of data analysis. Based on the analysis, for which all the calculated values are above the critical value, the alternate hypotheses which states that ethics should be taught as a separate course from principle of auditing and that teaching accounting ethics will help instill the culture of ethics in the student accountants were accepted. From the findings, the paper concludes that if ethics is taught well as an independent course in the accounting curriculum and not as part of auditing, the future accountant is bound to have instilled in him her, the required ethical culture.